FOCUS ON SLEEP PROBLEMS IN PATIENTS WITH SOMATOFORM DISORDERS - Skrypnikov, A.M.; Rakhman, L.V.; Markova, M.V.; Shpylovyi, I.V.; Plevachuk, O.Yu. (World of Medicine and Biology, 2019)
One of the most important non-specific symptoms of the somatoform disorders is sleep disturbance. The existence of direct correlations between the intensity of pain and other unpleasant bodily sensations and the duration and intensity of sleep disturbances has been proved. The purpose of the study was to analyze the sleep function in patients suffering from somatoform disorders and to develop a complex medical care system for such patients. 96 outpatient subjects with a diagnosis of somatoform disorder (F.45 by ICD-10) were examined. The list of Robbins symptoms was used for a clinical evaluation; Hamilton Rating Scale for Depression was used to assess the emotional state of patients. Ananalysis of the presence and intensity of sleep disorders was conducted on the Pittsburgh Sleep Quality Index. Patients received SSRI antidepressants as a basict herapy. Patients of the treatment group were additionally treated with cinazepam. A significant improvement in sleep quality from the therapy beginning in patients from the treatment group receiving combined treatment (SSRI antidepressants and cinazepam) was showed, which correlated with a significant decrease in the intensity of depressive symptoms in this group. The combined use of SSRI antidepressants and cinazepam significantly affects the rate of reduction of sleep disorders, unpleasant somatic sensations, as well as symptoms of mental and somatic anxiety, reduces the severity of depressive-hypochondriac symptoms, improves mood and quality of life of patients with somatoform disorders.